Investigation of Suitable MAC Protocols for Optical Wireless Body-Area Networks - Giachoudis, Christos; Khalighi, Mohammad Ali; Zvanovec, Stanislav; Papanikolaou, Vasileios; Tegos, Sotiris A.; Karagiannidis, George K. (2024 14th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP), 2024)
We consider the use of optical wireless data transmission from the medical nodes in wireless body-area networks (WBANs) for monitoring a patient's vital signs. To investigate efficient medium-access control (MAC) protocols, we contrast the two developed standards of IEEE 802.15.6 and IEEE 802.15.7 from the points of view of energy efficiency and latency. The first standard was originally developed for radio-frequency signal transmission, whereas the latter is based on the optical wireless technology. The comparison of the two protocols is made using the Castalia simulator and realistic optical WBAN channel models from previous work. This study also offers valuable insights into the performance of the latest IEEE 802.15.13 standard, designed for optical WBANs.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Castalia simulator; IEEE 802.15.13; IEEE 802.15.6; IEEE 802.15.7; optical wireless communications; patient monitoring; Wireless body-area networks